(untitled) (Global Journal of Medical Research, 2018)
This paper is concerned with the elastodynamic interactions of the ultra-laser heat source with homogeneous micro stretch-thermoelastic mass diffusion medium. The medium is under application of various forces. Normal mode analysis technique has been applied to the basic equations to solve the problem. Expressions are derived for normal stress, tangential stress, micro stress and temperature distribution. The numerically computed results have graphs also. The analysis of various stress quantities is there in this model. This research has some special cases from the present investigation.